Frontiers of South Asian culture : nation, trans-nation and beyond - Region/Nation/Trans-Nation: Literature-Cinema Interface (Conference) (2019 : Goa, India); Patra, Parichay, 1985-; Bhattacharya, Amitendu (New York, NY : Routledge, 2024)
"This book might be considered as one of the first of its kind in the subcontinent to concentrate so significantly on trans-nation, transnationalism and its dialogue with various nationalisms in South Asia. Taking the absence of discussion on transnationalism in South Asia as a crucial juncture as well as a point of intervention, this book intends to push the boundaries further by organizing a dialogue between the nation-state and many nationalisms and the emergent method of transnationalism. It opens itself up for many cross-border movements, formulating the trans-South Asian discursive exchange necessitated by contemporary theoretical upheavals. It looks at such exchanges through the prism(s) of literature and cinema and traces many modes of engagement that exist between some of the globally dominant literary and cinematic forms, trying to locate these engagements and negotiations across three geopolitical formations and locations of culture, namely region, nation and trans-nation"--
"This book owes its genesis to an international conference on the theme of 'Region/Nation/Trans-Nation: Literature-Cinema Interface' that was organized and hosted by the Department of Humanities and Social Sciences, Birla Institute of Technology and Science (BITS), Pilani - K.K. Birla Goa Campus, India, from 31 January to 2 February 2019"-- CIP galley.
Keywords: Transnationalism in motion pictures -- Congresses; National characteristics, South Asian, in motion pictures -- Congresses; Motion pictures -- South Asia -- History -- Congresses; South Asian literature -- History and criticism -- Congresses; Transnationalism in literature -- Congresses; National characteristics, South Asian, in literature -- Congresses; LITERARY CRITICISM / Asian / Indic; HISTORY / Asia / India & South Asia